Mechanism of Gelatinization in Milk Product after Addition of the Passion Fruit Juice by Analysis of the Physicochemical and Microsructural Properties - R. Malaka; . Hajrawati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The addition of certain fruit juices to milk products as a way to create new flavor has been known to also cause an interaction between the fruit juice and the components of the milk product. The mechanism of gelatinization in milk products as a result of adding the passion (Passiflora edulis Sims) fruit juice and by processing methods like heating and acidity will influence the final milk product. In this study, the mechanism of gelatinization is established through the observation of the products’s microstructure. This study was arranged factorially according to Completely Randomised Design. The first factor was passion fruit juice concentration (7.5 and 10%) and the second factor was ripening time (0, 1, 2 and 3 weeks). The variables observed were physical properties, which was done by the measurement of pH and lactic acid concentration. The changes in physical properties were monitored by observation of product microstructure by light microscopic with histopathological technique. The best cheese product was achieved with a passion fruit juice concentration of 10%. The product observed had a more compact microstructure at a ripening time of 3 weeks with pH of 4,29 and lactic acid percentage of 1.27